Partial discharge ultrasonic detection based on EULER-MUSIC algorithm and conformal array sensor - Pang, Xianhai; Wu, Han; Li, Xiaofeng; Qi, Yanxun; Jing, Hao; Zhang, Jiantao; Xie, Qing (IET generation, transmission & distribution, 2018)
A conformal array sensor suitable for partial discharge (PD) detection of electrical equipment was designed which displays multiple characteristics including compatibility with the surface of any carrier without affecting the performance of the carrier. Taking a cylindrical conformal array as an example, the simulation model was given and the array flow pattern of the cylindrical conformal array sensor was determined. Based on the Euler transform, the algorithm of multiple signal classification (MUSIC) was improved. An algorithm of array signal direction finding suitable for conformal array sensors was proposed and its performance under different signal-to-noise ratios and different array elements was simulated. The improved algorithm and conformal array sensor were used to simulate and test the PD signal. The results show that the algorithm and the conformal array sensor are suitable for PD detection of electrical equipment.